An unusual cause of pulmonary embolism following blunt chest trauma: a case study - Garg,Shweta (2024)
Abstract Introduction: Chest injury resulting from thoracic trauma experienced by an individual is presented in this study. The results obtained from this analysis conducted retrospectively are anticipated to contribute to raising awareness of early diagnosis of embolism in the context of trauma. Objective: Pulmonary embolism remains a disease that needs clinical suspicion to prevent mortality and morbidity. More so in young individuals, suspicion is very low as compared to old age individuals with multiple co-morbid conditions. There is a high risk of mortality associated with Pulmonary embolism in case of not detected and treated in the early stage. Methods: This document outlines a case study involving a young male patient who exhibited sudden breathlessness after experiencing blunt chest trauma. The patient was diagnosed with pulmonary thromboembolism later on. Results: The patient was discharged on the novel oral anticoagulant Rivaroxaban. It is one of the first available direct factor Xa inhibitors, recommended for use in venous thromboembolism. It allows predictable anticoagulation, and routine coagulation monitoring is not required, unlike warfarin. Conclusion: The authors concluded that the development of a hypercoagulable state leads to the occurrence of pulmonary embolism triggered by epithelial injury following a traumatic event. In the case of submissive pulmonary embolism, catheter-directed thrombolysis is considered useful when systemic thrombolysis poses a potential risk of hemorrhage.